A review of urinary angiotensin converting enzyme 2 in diabetes and diabetic nephropathy - Gilbert, Akankwasa (Array, 2018)
Urinary angiotensin converting enzyme 2 (ACE2) is significantly increased in diabetes and diabetic nephropathy. While studies on its clinical significanceare still underway, its urinary expression, association with metabolic and renal parameters has been in the recent past considerably studied.The recent studies have demystified urine ACE2 in many ways and suggested the roles it could play in the management of diabetic nephropathy. Inall studies the expression of urinary ACE2 was determined by enzyme activity assay and/with the quantification of ACE2 protein and mRNA by methodswhose reliability are yet to be evaluated. This review summarizes recent findings on expression of urinary ACE2, examines its relationship withclinical parameters and highlights possible applications in management of diabetic nephropathy.